Effect of RuO2 in the shape selectivity of submicron-sized SnO2 structures - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Journal of Physical Chemistry B, 2005)
Several dissimilar types of tin oxide microstructures including bipyramids, cubes, and wires synthesized effectively by means of a simple approach were investigated using X-ray diffraction (XRD), thermogravimetry/ differential thermometric analysis (TG-DTA), and X-ray photoelectron spectroscopy (XPS). A possible growth mechanism is proposed using the results of these studies. The texture coefficient values of all the structures, indexed to a tetragonal lattice, exhibit amazing variation in the preferred orientation with respect to their shapes. Although XPS data indicate that wires and cubes have a strong SnO2 type signal, bipyramids interestingly exhibit both SnO and SnO2 signals and a correlation of the binding energy helps in understanding the growth kinetics of such submicron structures. The. results suggest that the bipyramids are formed because of the vapor-solid process (VS) while wires and cubes are formed by the vapor-liquid-solid (VLS) progression.

Growth kinetics and thermodynamic stability of octadecyltrichlorosilane self-assembled monolayer on Si (100) substrate - Kulkarni, S. A.; Mirji, S. A.; Mandale, A. B.; Gupta, R. P.; Vijayamohanan, K. P. (Materials Letters, 2005)
We have studied the growth kinetics and thermodynamic stability of octadecyltrichlorosilane (OTS) self-assembled monolayers on Si (100) substrate in order to understand its role in controlling the adhesion and surface hydrophobicity. Time-dependent contact angle measurements, using water as a function of OTS concentration, show rapid monolayer formation in the initial stage followed by a slow attainment of full coverage and the overall kinetics approximately follows the Langmuir adsorption isotherm. The adsorption rate constant (k(a) = 150 M-1 s(-1)) is found to be significantly greater than the desorption rate constant (k(d) = 0.156 s(-1)) while the Gibbs free energy (Delta G(ads)) change amounts to -4.2 kcal/mol suggesting thermodynamic stability of OTS monolayer on a silicon surface. Partial monolayer formation by a `uniform' growth mechanism, even at low coverage, is revealed by atomic force microscopy (AFM) in conjunction with grazing angle FTIR spectroscopy. Analysis of the interfacial adhesion properties using Zisman plot suggests a critical surface tension (gamma(c)) of 20.7 dyn/cm for OTS monolayer on Si (100) surface. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Gibbs's free energy (AG); growth kinetics; octadecyltrichlorosilane (OTS); self-assembled monolayers (SAMs); Zisman plot

Room temperature nitric oxide sensor actualized from Ru-doped SnO2 nanowires - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Sensors and Actuators B - Chemical, 2005)
We report synthesis of the novel Ru-doped SnO2 nanowires and their distinctive response towards NO., and liquefied petroleum gas (LPG) in air. These nanowires have been prepared by a simple approach of evaporation of metal oxide at elevated temperature, The sensor exhibits three order of magnitude changes in the conductivity on exposure to NO2 in air at room temperature, Furthermore. Ru being one of the excellent sensitizers towards LPG these wires also exhibits sensitivity at 250&DEG; C. The amount of Ru plays a crucial role in modulating the sensitivity and lowering the operating temperature. © 2005 Elsevier B.V. All rights reserved.
Keywords: LPG; Nanowires; NO2; tin oxide ruthenium oxide

Temperature-induced phase transitions of the ordered superlattice assembly of Au nanoclusters - Chaki, N. K.; Vijayamohanan, K. P. (Journal of Physical Chemistry B, 2005)
Superlattices of monolayer protected metallic and semiconducting nanoclusters have attracted significant attention due to their promising applications in nanotechnology. In this paper, we investigate the effect of temperature on the ordered superlattice structure of relatively larger sized An nanoclusters passivated with dodecanethiol [ca. Au-1415(RS)(328)] with the help of in situ temperature controlled X-ray diffraction (XRD) and infrared spectroscopy (IR) in conjunction with thermogravimetric (TG) and differential scanning calorimetric (DSC) analysis. In brief, monolayer protected Au nanoclusters (AuMPC) were prepared by a modified Brust synthesis technique, where dodecanethiol itself acts as both phase transfer and simultaneous capping agent during the reduction process, generating an average particle size of 3.72+/-0.4 nm after repeated solvent extraction and careful fractionation experiments. These particles are characterized with the help of UV-vis, transmission electron microscopic (TEM), IR, and NMR techniques, where effective capping as well as the superlattice formation on the TEM grid is evident from the combined analysis of these results. In situ low-angle XRD analysis shows that the particles undergo an irreversible phase transition in the temperature range of 100-115degreesC, which is also reflected in the data from in situ IR analysis. However, the DSC analysis does not account for this phase transition, although the reversible phase transition due to the alkyl chain dynamics is in good agreement with the previously reported results. These results indicate the formation of temperature-induced, diffusion-limited phase transition involving nonequilibrium fractal structures, which is in good agreement with the previous available theoretical studies. The determination of the temperature window for the stability of these ordered assemblies would be used to understand the effect of thermal stress for device applications.

Directed organization of gold nanoclusters on silver nanowires: a step forward in heterostructure assembly - Sharma, J.; Vivek, J. P.; Vijayamohanan, K. P.; Singh, P.; Dharmadhikari, C. V. (Applied Physics Letters, 2006)
We investigate the directed assembly of tridecylamine protected gold nanoclusters of 4-5 nm size on functionalized silver nanowires of 55-60 nm diameter and the electron transfer behavior of this integrated structure using transmission electron microscopy, non-contact atomic force microscopy, and scanning tunneling microscopy/spectroscopy. Linear I-V for bare silver nanowire suggests metallic behavior but high tunnel resistance indicates presence of insulating layer on the surface. Identical I-Vs obtained for isolated gold nanoparticle and heterostructure suggests that electron transport across nanowires in the latter is governed by gold nanoparticles in contrast to expected ballistic or diffusive transport along their length.(c) 2006 American Institute of Physics.